Refractory Primary Sjögren Syndrome Successfully Treated With Bortezomib. Issue 1 (January 2015) - Jakez-Ocampo, Juan; Atisha-Fregoso, Yemil; Llorente, Luis
Abstract : Abstract: Primary Sjögren syndrome (PSS) is a chronic autoimmune disease characterized by sicca complex and various systemic manifestations. Although it is well accepted to use corticosteroids for the treatment of systemic manifestations, there is scarce information available regarding the use of targeted therapy for refractory cases. We describe a case of a severe PSS patient refractory to conventional treatment with a response to bortezomib, a proteasome inhibitor commonly used for the treatment of multiple myeloma. Bortezomib administration resulted in a notable improvement of the general symptoms, particularly fatigue, and a decrease in serum globulin levels as well as in serum viscosity. Hyperglobulinemic purpura disappeared, and prednisone tapering succeeded. Because of chronicity, no clinical changes were observed in sicca symptoms. As far as we know, this is the first report on the use of bortezomib in a refractory case of PSS